Genetic Mosaicism in Calmodulinopathy. (September 2019) - Wren, Lisa M.; Jiménez-Jáimez, Juan; Al-Ghamdi, Saleh; Al-Aama, Jumana Y.; Bdeir, Amnah; Al-Hassnan, Zuhair N.; Kuan, Jyn L.; Foo, Roger Y.; Potet, Franck; Johnson, Christopher N.; Aziz, Miriam C.; Carvill, Gemma L.; et al.
Abstract : Background: CaM (calmodulin) mutations are associated with congenital arrhythmia susceptibility (calmodulinopathy) and are most often de novo. In this report, we sought to broaden the genotype-phenotype spectrum of calmodulinopathies with 2 novel calmodulin mutations and to investigate mosaicism in 2 affected families. Methods: CaM mutations were identified in 4 independent cases by DNA sequencing. Biochemical and electrophysiological studies were performed to determine functional consequences of each mutation. Results: Genetic studies identified 2 novel CaM variants ( CALM3 -E141K in 2 cases; CALM1 -E141V) and one previously reported CaM pathogenic variant ( CALM3 -D130G) among 4 probands with shared clinical features of prolonged QTc interval (range 505–725 ms) and documented ventricular arrhythmia. A fatal outcome occurred for 2 of the cases. The parents of all probands were asymptomatic with normal QTc duration. However, 2 of the families had multiple affected offspring or multiple occurrences of intrauterine fetal demise. The mother from the family with recurrent intrauterine fetal demise exhibited the CALM3 -E141K mutant allele in 25% of next-generation sequencing reads indicating somatic mosaicism, whereas CALM3 -D130G was present in 6% of captured molecules of the paternal DNA sample, also indicating mosaicism. Two novel mutations (E141K and E141V) impaired Ca 2+ binding affinity to the C-domain of CaM. Human-induced pluripotent stem cell-derived cardiomyocytes overexpressing mutant or wild-type CaM showed that both mutants impaired Ca 2+ -dependent inactivation of L-type Ca 2+ channels and prolonged action potential duration. Conclusions: We report 2 families with somatic mosaicism associated with arrhythmogenic calmodulinopathy, and demonstrate dysregulation of L-type Ca 2+ channels by 2 novel CaM mutations affecting the same residue. Parental mosaicism should be suspected in families with unexplained fetal arrhythmia or fetal demise combined with a documented CaM mutation. Abstract : Supplemental Digital Content is available in the text.